'The Army of Railwaywomen', 1942 (pg. 1) (1942)
1942 1939-1945 "'The Army of Railwaywomen', 1942 (pg. 1)" [hfr0170], 1942 This press release from the Railway Executive Committee details the work undertaken by 100,000 women on the railways during the war.